Exploring the Depths of Marine Biotechnology: Discoveries, Diversity, and Future Horizons - Mishra, Manoj K.; Shukla, Ajay Kumar; Dev, Suresh Kumar; Ahmad, Razi (Current Biotechnology, 2024)
Among the various technological advancements in different fields that help fulfill our needs further, marine biotechnology is one that has brought a significant change in the overall bleak outlook of the limited resources that the oceans have to offer. Marine biotechnology has not just revolutionized the method of farming and increased productivity, but it has also ensured a consistent supply to various cuisines throughout the world. In recent years, marine biotechnology has outgrown its traditional image in the seafood-related industry to one that caters to a plethora of industries such as enzyme technology, pharmaceuticals, tanning industry, cancer therapeutics, cosmetic industry, biodegradable polymers, and bioremediation. These are a few among a broad spectrum of industries where it finds applications and many more are yet to be explored. Remarkably, marine biotechnology has not only helped restore the normal local flora and fauna of the oceans but has also contributed extensively to conservation efforts. In this review, an attempt has been made to follow the trails of the wide applicability of marine biotechnology as well as its impact on various sectors in recent years.
Keywords: seafood